Synchrony or asynchrony: development of facial expression recognition from childhood to adolescence based on large-scale evidence - Wang, Yihan; Luo, Qian; Zhang, Yuanmeng; Zhao, Ke (Frontiers in Psychology, 2024)
The development of facial expression recognition ability in children is crucial for their emotional cognition and social interactions. In this study, 510 children aged between 6 and 15 participated in a two forced-choice task of facial expression recognition. The findings supported that recognition of the six basic facial expressions reached a relatively stable mature level around 8–9 years old. Additionally, model fitting results indicated that children showed the most significant improvement in recognizing expressions of disgust, closely followed by fear. Conversely, recognition of expressions of happiness and sadness showed slower improvement across different age groups. Regarding gender differences, girls exhibited a more pronounced advantage. Further model fitting revealed that boys showed more pronounced improvements in recognizing expressions of disgust, fear, and anger, while girls showed more pronounced improvements in recognizing expressions of surprise, sadness, and happiness. These clear findings suggested the synchronous developmental trajectory of facial expression recognition from childhood to adolescence, likely influenced by socialization processes and interactions related to brain maturation.